PENGEMBANGAN MEDIA PEMBELAJARAN POWERPOINT INTERAKTIF PADA MATA PELAJARAN IPAS SISWA KELAS III B DI UPTD SD INPRES PERUMNAS 2 - Advenya Tecing Putri, Priskalia; Nama Koten, Angelikus; Elisabet Antoneta Nawa, Netty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop an interactive PowerPoint-based learning media for the Natural and Social Sciences (IPAS) subject on the topic of landforms for third-grade elementary school students. The background of this study is based on the low level of student engagement and participation in learning, which is still dominated by lecture methods and the use of less varied media. Therefore, innovative or interactive learning media are needed to improve the quality of the learning process. This study employed the Research and Development (R&D) method using the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The subjects of this study included media experts, material experts, teachers, and third-grade students. Data were collected through observation, interviews, questionnaires, and tests. The data were analysed using descriptive quantitative methods to determine the validity, practicality, and effectiveness of the developed learning media. The results of the study indicate that the interactive PowerPoint learning media achieved a validity level of 93.56% (very valid), a practicality level of 96.93% (very practical), and an effectiveness level of 90% (very effective). These results indicate that the developed learning media can improve students’ understanding and engagement in the learning process. In conclusion, the interactive PowerPoint learning media developed in this study is feasible to be used as an alternative learning media to enhance the quality of learning on the topic of landforms in elementary schools. Keywords: learning media, interactive PowerPoint, IPAS